Greener synthesis of 1, 2, 3-triazoles using a copper(i)-exchanged magnetically recoverable β-zeolite as catalyst. (25th August 2020) - Costa, Elizama R.; Andrade, Floyd C. D.; de Albuquerque, Danilo Yano; Ferreira, Luanne E. M.; Lima, Thiago M.; Lima, Carolina G. S.; Silva, Domingos S. A.; Urquieta-González, Ernesto A.; Paixão, Márcio W.; Schwab, Ricardo S.
Abstract : A novel magnetically recoverable Cu(i )-exchanged β-zeolite catalyst was prepared, characterized and applied for the synthesis of 1, 2, 3-triazoles via the one-pot three-component reaction. Abstract : Herein, we describe the preparation and thorough characterization of a novel magnetically recoverable copper(i )-exchanged β-zeolite and its use as an efficient catalyst for the synthesis of 1, 2, 3-triazoles via the one-pot three-component reaction of organic halides, terminal acetylenes, and sodium azide in water. The magnetically recoverable β-zeolite could be easily separated from the reaction mixture with the aid of a magnet and reused in several consecutive reactions. Importantly, a series of characterizations studies allowed us to disclose the mechanism for the deactivation of the catalyst, and therefore to propose a method for its reactivation.